PENGARUH KOMPLEKSITAS TEKNOLOGI, INTERDEPENDENSI, Dan DESAIN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA BANK PERKREDITAN RAKYAT - Mahsina .; Asmie Poniwati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
This study aims to determine whether there is a partial influence on the complexity of technology, interdependence, and design of Accounting Information Systems on the performance of Rural Credit Banks (BPR) in Boyolali, to find out whether there are simultaneous influences on technological complexity, interdependence and design of Accounting Information Systems on Bank performance Perkreditan Rakyat (BPR) in Boyolali, and finally to find out whether the variable complexity of technology has a dominant influence on the performance of Rural Credit Banks (BPR) in Boyolali. This research was conducted at BPRs in Boyolali, out of 27 BPRs in Boyolali that are in accordance with BI data, but 10 BPRs in Boyolali could be selected for research. The sample selection process in this study began with the distribution of 60 questionnaires to 10 rural banks in Boyolali, and each rural bank was given 6 questionnaires. Based on the results of data analysis, it was concluded that the variable technological complexity (X1), interdependence (X2), and the design of Accounting Information Systems (X3) had a positive effect on the performance of BPR (Y). And the most dominant variable is the interdependence variable (X2), because it has the largest Beta Standardized coefficient, which is equal to 0.517 or 51.7%.